Brain-heart autonomic axis across different clinical status and severity of chronic obstructive pulmonary disease - Castello-Simões, Viviane (2021)
Purpose: Impairment of cardiac autonomic integrity is common in chronic obstructive pulmonary disease (COPD) patients. The influence of the interaction between clinical and severity status on brain-heart autonomic axis (BHAA) is not well known. We aimed to investigate the BHAA function across different clinical status and severity of COPD. Methods: Cross-sectional study involving 77 COPD patients allocated into four groups according to clinical status [acute exacerbation (GAE) or stable (GST)] and severity [less (-) or more (+)]: 1) GAE-, n = 13; 2) GAE+, n = 20; 3) GST-, n = 23; and 4) GST+, n = 21. Heart rate variability (HRV) at rest and heart rate recovery (HRR) after 6-min walk test were markers of BHAA. Mean R-R, STDRR, RMSSD, RRtri, HF, LF, SD1, SD2, ApEn and SampEn were the HRV indexes and, HRR was obtained as: HR at 1st min of recovery minus peak HR. Results: A main effect of clinical status (p < 0.001) was found to vagal modulation in GAE-vs. GST- (RMSSD: 25.0 ± 14.8 vs. 12.6 ± 5.5 ms; SD1: 18.0 ± 10.6 vs. 8.9 ± 3.9 ms) and to GAE + vs. GST+ (RMSSD: 26.4 ± 15.2 vs. 15.4 ± 6.3 ms; SD1: 18.3 ± 11.2 vs. 10.9 ± 4.5 ms). An effect of clinical status (p = 0.032) and severity (p = 0.030) were found to HF (vagal) in GAE + compared to GAE- and GST+ (264.7 ± 239.0 vs. 134.7 ± 169.7 and 135.8 ± 139.7 ms2). Lower HRR was found in GAE-compared to GST- (8.0 ± 2.4 vs. 19.6 ± 2.4 bpm), p = 0.002. Conclusion: In COPD patients, clinical status (AECOPD or stable) was more dominant than the severity on BHAA function. A more pronounced parasympathetic modulation was found in AECOPD patients with a lower HRR to exercise.